Effect of static magnetic field on terrestrial isopods (Isopoda: Oniscidea). Issue 2 (4th January 2019) - Béjaoui, Mustapha; Khalloufi, Noureddine; Touaylia, Samir
Abstract: We assessed the effect of exposure of three terrestrial isopods, Armadillidium vulgare (Latreille, 1804 ), A. granulatum (Brandt, 1833 ), and Porcellio laevis Latreille, 1804, to a static magnetic field (SMF) (200 mT). Exposure altered mortality, reproduction, and behavior (volvation). Mortality rate increased significantly ( P < 0.05) in the three species as compared to non-exposed individuals. Volvation changed from euspheric to mesospheric in A. vulgare, and from mesospheric to the absence of volvation in A. granulatum ( P < 0.01). The size of the male copulatory organ and the female marsupium of P. laevis were significantly changed ( P < 0.001) after exposure to SMF and maintained until reaching maturity.